Iron–Sulfur Clusters in Chemistry and Biology. Volume 1: Characterization, Properties and Applications. Second edition. Edited by Tracey Rouault. De Gruyter, 2017. Pp. xv + 447. Price EUR 99.95, GBP 90.99, USD 114.99 hardcover, ISBN 978‐3‐11‐047850‐1. Issue 12 (4th December 2017) - Jacquot, Jean-Pierre
Abstract : A review of Iron–Sulfur Clusters in Chemistry and Biology. Volume 1 edited by Tracey Rouault. Abstract : A review of Iron–Sulfur Clusters in Chemistry and Biology. Volume 1 edited by Tracey Rouault.